Peningkatan Keterampilan Berpikir Kreatif pada Project Pembuatan Kerajinan Serat Mendong Tasikmalaya, Jawa Barat - Sakilah Fatimah Nugraha; Tri Wahyu Agustina; Epa Paujiah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to analyze the improvement of students' creative thinking skills through the implementation of project-based learning integrated with the Environmental-STREAM approach in the topic of plant structure and tissues by utilizing the local potential of mendong fiber (Fimbristylis globulosa). The research was conducted at a public senior high school in Tasikmalaya Regency in April 2026. A quasi-experimental approach with a Static Group Pretest-Posttest Design was employed. The sample was selected using a purposive sampling technique, resulting in an experimental group consisting of 38 students who participated in Project-Based Learning (PjBL) integrated with Environmental-STREAM and a control group consisting of 40 students who participated in conventional PjBL. Data were collected using a creative thinking skills test instrument covering the indicators of fluency, flexibility, originality, and elaboration. The data were analyzed using the N-Gain test based on established classification criteria. The results indicated that the experimental group achieved an average N-Gain score of 0.72, which was categorized as high, while the control group obtained an N-Gain score of 0.69, categorized as moderate. Indicator-based analysis revealed that fluency achieved the highest score of 0.76, whereas originality showed the lowest score of 0.68. Based on these findings, it can be concluded that project-based learning integrated with the Environmental-STREAM approach through mendong fiber craft-making activities was effective in enhancing students' creative thinking skills compared with conventional learning. Keywords: Creative Thinking Skills, Environmental-STREAM, Local Potential, Mendong Fiber, Project-Based Learning